Ketamine Anaesthesia for Paediatric Ophthalmology Surgery - Rana, Suraj SJB; Pun, Madhu Sudan; Thakur, Jaya; Poudyal, Govinda; Gurung, Reeta; Good, William V; Ruit, Sanduk (Medical Journal of Shree Birendra Hospital, 2002)
Ketamine Anaesthesia for Paediatric Ophthalmology Surgery